IMPLEMENTATION OF THE GARPUTALA METHOD AS A QUR'ANIC COUNSELING AND LEADERSHIP MODEL FOR BUSINESS PEOPLE - Ahmad Sulthoni; Wiji Lestari; Kerwanto (LPPM Institut Nida El-Adabi, 2024)
This study aims to examine the implementation of the Garputala method as a Qur'anic counseling and leadership model in supporting business people to face various problems effectively and affordably. Using a qualitative approach with a case study method, data was obtained through interviews with alumni of Magnet Rezeki Training in the Bumi Serpong Damai area. The results showed that the Garputala method helps business people achieve emotional calmness and positive behavioral changes. In addition, the application of Qur'anic leadership through this method is proven to increase business turnover and provide solutions to mental problems and work productivity. The findings also demonstrate the potential of the Qur'an as an effective counseling medium for individual and organizational development. This research makes a practical contribution in introducing a spiritually-based approach that is relevant for the business world, while opening up opportunities for exploration of similar methods in other educational and social fields.